The interplay of type I interferon, NLRP3 inflammasome, and self-antigen clearance in systemic lupus erythematosus progression - Rahmadhanita, Putri; Finalita, Floera; Ariefani, Salsabila (Institute of Computer Science (IOCS), 2026)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease driven by impaired cellular debris clearance. While individual inflammatory pathways are well-documented, their synergistic interactions lack comprehensive synthesis, hindering the development of mechanism-based therapeutics. This literature review aims to elucidate the interconnected roles of specific cellular inflammatory pathways and their positive feedback loops in driving the clinical progression of SLE. A comprehensive literature review was conducted by analyzing 35 peer-reviewed scientific studies published between 2015 and 2025, sourced primarily from the PubMed database, focusing on SLE pathogenesis, cellular inflammation, and disease severity. SLE progression is propelled by a mutually reinforcing inflammatory cascade rather than isolated pathways. We identified three primary components establishing a pathological positive feedback loop: (1) Impaired self-antigen clearance, supplying a continuous source of Damage-Associated Molecular Patterns (DAMPs); (2) Type I Interferon (IFN-I) overactivation, acting as the systemic immune response conductor; and (3) The NLRP3 inflammasome, functioning as a local amplifier that induces direct tissue damage. The identification of this synergistic feedback loop demonstrates that single-target interventions may be insufficient. Comprehending this dynamic cascade necessitates a paradigm shift towards precision medicine. Future therapeutic strategies must prioritize multi-target combination therapies, stratifying patients based on their unique biological profiles to disrupt the pathogenic cycle effectively.